Effect of transcranial direct-current stimulation on executive function and resting EEG after stroke: A pilot randomized controlled study. (September 2022) - Wang, Zhengtao; Li, Jie; Wang, Xianglong; Liu, Sishi; Wu, Wen
Highlights: Explore the effect of t-DCS on executive function among stroke patients. This randomized controlled study was single-blind. Explore the recovery mechanism of PSEI patients based on EEG. Abstract: Background: The effects of transcranial direct current stimulation (tDCS) on post-stroke executive impairment (PSEI) remain controversial. Resting state electroencephalogram (EEG) can assist in the diagnosis and assessment of executive dysfunction. Objectives: We aimed to use EEG to explore the effect of tDCS on executive function among stroke patients. Methods: Twenty-four patients with PSEI were randomly divided into experimental and control groups, which received real and sham stimulation, respectively. Anodal electrical stimulation was applied to the left dorsolateral prefrontal lobe (F3). The stimulation intensity was 2 mA for 20 min once daily for 7 days. Executive function was monitored using neuropsychological scales. Results: The experimental group outperformed the control group in clinical scale results, with significant differences in the following scores: symbol digital modalities test, TMT-A, TMT-B, and digital span test. In the left central zone, theta band power was significantly higher after anodal electrical stimulation than before. Analysis of the correlation between EEG power and psychometric scores revealed that the power change was positively correlated with the scores on the symbol digital modality test (r = 0.435, p < 0.05). Conclusion: Anodal tDCS can enhance executive function in patients with PSEI, and tDCS-related improvements are related to the enhancement of theta power in the affected region.